Enhanced mechanical properties of boron nitride nanosheets/copper composites with a bioinspired laminated structure. Issue 9 (2nd September 2022) - Wang, Yun; Huang, Can; Li, Ruitao; Liu, Hong; Xu, Zhenying; Yu, Chao; Li, Hua
ABSTRACT: Poor mechanical properties of copper (Cu) hinder its applications as structural materials. Developing bioinspired-laminated structure is among the most promising strategies for obtaining modern structural materials with excellent combination mechanical properties. To explore the possibility of enhancing mechanical properties of Cu, herein, we fabricated boron nitride nanosheets/copper (BNNSs/Cu) composites with a bioinspired laminated structure, achieved by ball milling and spark plasma sintering (SPS). Their mechanical properties were investigated. The results indicate that their tensile strength and toughness are both larger than those of pure Cu: the addition of 0.3 vol% of BNNSs improves the tensile strength from 187 MPa to 216 MPa and the elongation from 41% to 56%, respectively. The enhancement of ductility is due to the unique lamellar distribution of BNNSs in composites, which resulted in retarding cracks propagation; the strengthening effect of BNNSs is determined by the moderate interfacial bonding strength and possible agglomeration of BNNSs. Graphical Abstract: uf0001